Determinación del grado de metalización de pellets de mezclas de minerales de hierro reducidos en horno Linder (2016)
This work corresponds to a study on pellet reduction formed from mixtures of iron ore from Topaipí (Department of Cundinamarca, Colombia) with two iron ores coming from Cerro San Isidro and Cerro Altamira (State of Bolivar, Venezuela). This ferrous mineral benefaction technique has been used for several decades in the steel industry in order to recover fine materials, generated in the processes previous to their use; which in actuality mixtures are made between low grade and high grade metal are created. These iron ore metals, mixtures, and the components to be added to make the pellets were categorized by their chemical, physical, and mineralogical components through X-ray diffraction and chemical analysis. After drying, the pellets were reduced in the laboratory in a Linder furnace at 850 and 1000°C during 160 minutes. The purpose was to evaluate the degree of metallization and basicity indices of the direct reduced iron (DRI). This was done in order to partially substitute the scraps in the electric arc furnace and consequently, make ferrous products. The analysis showed that the mixtures increase the iron content and better the basicity indices. A metallization degree of 81.20 and 95.1% were obtained. This demonstrates that the ratio of mineral used in the mixture, taking into account the chemical composition of the minerals and the contents added in the production of the mixture, is appropriate and the DRI obtained meet the expected specifications.